Scheduling controller for microgrids energy management system using optimization algorithm in achieving cost saving and emission reduction - Roslan M.F.; Hannan M.A.; Jern Ker P.; Begum R.A.; Indra Mahlia T.M.; Dong Z.Y. (Elsevier Ltd, 2023)
Carbon dioxide; Controllers; Cost effectiveness; Cost reduction; Emission control; Energy management systems; Energy resources; Learning algorithms; Operating costs; Power management; Cost saving; Distributed Energy Resources; Emission reduction; Energy; Management systems; Micro grid; Optimization algorithms; Optimized controllers; Scheduling controllers; Uncertainty; Scheduling; algorithm; carbon dioxide; energy resource; lightning; optimization; smart grid; Malaysia; Perlis; West Malaysia